Perilaku 3R pada Konsumen yang Sudah Meretur Baju Blazer di Toko Flyco Jogja - Desti Fitria Suci; Arundati Shinta; Amin Al Adib (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2024)
Yogyakarta City is one of the largest contributors of waste to the Piyungan landfill, highlighting the need to increase environmental awareness among the community. This study aims to describe the 3R (reduce, reuse, recycle) behavior of consumers who return blazer jackets at Flyco Store Jogja. A qualitative method with in-depth interviews and data triangulation was applied to two subjects, male and female, with middle to upper socioeconomic status. The results show that both subjects practice 3R behaviors with different levels of consistency. The female subject is more active in applying 3R behaviors compared to the male subject, who is more influenced by his wife’s role. These findings support the Kuznets Curve theory related to increased environmental awareness among certain income groups. The ecofeminism approach reveals that women have higher empathy and care for the environment due to domestic roles and emotional closeness. The study’s implications emphasize the importance of considering gender and personal awareness factors in promoting 3R behavior among fashion product consumers.